Synthesis and characterization of polycaprolactone-carbon nanotube biocomposite fibres. - Tan, Grace Wan Chiu. (2009)
In this study, we attempt to investigate the effect of the addition of fillers into a polymer matrix. The fillers chosen for the study is Carbon nanotubes (CNTs). Carbon nanotubes are chosen as they have high tensile strength. MWCNT/PCL fibre composites have an increase in tensile strength compared to the neat PCL fibres. The neat PCL fibres had an ultimate tensile stress of 1.4248 MPa, while the PCL fibres with 5% MWCNTs incorporated had an increase in ultimate tensile stress with a value of 7.59006 MPa. The Young’s modulus of the MWCNT/PCL composites is measured and compared with the Young’s modulus of the neat PCL fibres. Through this comparison, the Young’s modulus of the MWCNTs used can be determined. In this experiment, the fibres were produced by electrospinning, and the fibres fabricated were subjected to tensile tests. It was found that with an increasing amount of MWCNT incorporated into the polymer matrix, the greater the Young’s modulus of the composite fabricated. The composite with 5% MWCNTs incorporated had a Young’s modulus of 66.225 MPa compared to that of the neat fibre having a Young’s modulus of 6.8818 MPa. This shows the reinforcing effect that the MWCNTs had on the strength of the composites. Using the Rule of mixtures, the Young’s moduli of the MWCNTs used were calculated and it was found to 9306.698 MPa.